Development and comparison of field assisted sintering techniques to densify CeO2 ceramics. Issue 14 (November 2022) - Harrison, R.W.; Morgan, J.; Buckley, J.; Bostanchi, S.; Green, C.; White, R.; Pearmain, D.; Abram, T.; Goddard, D.T.; Barron, N.J.
Abstract: Cerium dioxide (CeO2 ) was densified by conventional and field assisted sintering techniques in order to examine the effect of a range of sintering parameters on the resultant pellet microstructure, namely: temperature, hold time, atmosphere, electric field strength and polarity. CS at 1400 °C for 2 h in static air atmospheres provided the highest densities and grain sizes compared with an argon atmosphere, due to the retention of near stoichiometry maintaining sintering kinetics. SPS produced dense ceramics at similar sintering temperatures (1300 °C), but with greatly reduced sintering hold (5 min) and cycle times. However, microstructural inhomogeneity arose from the direct current polarity which led to oxygen ion diffusion toward the positive electrode. FS was performed with an alternating current electric field and produces samples of comparable density at sintering temperatures of 1100 °C for a hold time of around 1 h with no inhomogeneity due to the alternating current employed.